2017
DOI: 10.3390/met7020057
|View full text |Cite
|
Sign up to set email alerts
|

The BCC/B2 Morphologies in AlxNiCoFeCr High-Entropy Alloys

Abstract: Abstract:The present work primarily investigates the morphological evolution of the body-centered-cubic (BCC)/B2 phases in Al x NiCoFeCr high-entropy alloys (HEAs) with increasing Al content. It is found that the BCC/B2 coherent morphology is closely related to the lattice misfit between these two phases, which is sensitive to Al. There are two types of microscopic BCC/B2 morphologies in this HEA series: one is the weave-like morphology induced by the spinodal decomposition, and the other is the microstructure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(47 citation statements)
references
References 43 publications
(68 reference statements)
3
34
0
1
Order By: Relevance
“…Figure 3e shows the interior of the dendrites at x = 1.16 in greater detail, revealing spherical particles embedded in the matrix. Figure 3f, obtained from the interdendritic region for the same composition, shows a weave-like structure typical of spinodal decomposition, consistent with prior observations [14]. Figure 4e and 4f shows the EBSD results for x = 0.69.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Figure 3e shows the interior of the dendrites at x = 1.16 in greater detail, revealing spherical particles embedded in the matrix. Figure 3f, obtained from the interdendritic region for the same composition, shows a weave-like structure typical of spinodal decomposition, consistent with prior observations [14]. Figure 4e and 4f shows the EBSD results for x = 0.69.…”
Section: Resultssupporting
confidence: 86%
“…Intermediate VEC values would include a mixture of the two phases. These three parameters are calculated for the compositions in the present work (using the definitions and elemental values found in Guo et al [20]) and compared with those for the compositions examined in the prior studies in Figure 8 [11,13,14]. While the two phase regime sits within Guo et al's predicted range, all 4 sets of data exhibit narrower FCC+BCC/B2 ranges than predicted.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…They found that the homogenized alloy has a better hot workability than as-cast alloy, and the flow stress in a homogenized state was always higher than that in an as-cast state under the same deformation conditions. Ma et al [9] studied the morphological evolution of the body-centered-cubic (BCC)/B2 phases in Al x CoCrFeNi (x = 0.41, 0.57, 0.74, 0.92, 1.12, and 1.33) HEAs. They found that the BCC/B2 coherent morphology is closely related to the lattice misfit between these two phases: A weave-like morphology induced by the spinodal decomposition forms at lower Al contents, and spherical disordered BCC precipitates form within the ordered B2 matrix at much higher Al contents.…”
Section: Contributionsmentioning
confidence: 99%